Comparative Study of Short-Term Outcome between Laser Hemorrhoidoplasty and Milligan-Morgan Hemorrhoidectomy (IAHS Medical Journal, 2023)
Background: Due to the fear of postoperative pain and complications associated with open Milligan-Morgan (MM) surgery, mildly symptomatic patients often hesitate and delay undergoing surgical treatment for internal haemorrhoids. Laser Hemorrhoidoplasty (LHP) has been gaining popularity recently in the management of hemorrhoid. This study aimed to evaluate the efficacy of the LHP compared with MM surgery in the management of internal haemorrhoids.Materials and methods: This multi-center, open label, randomized controlled trial included 60 patietns with secondand third-degree internal haemorrhoids. The patients were randomized in a 1:1 ratio to receive either LHP (Group I) or conventional MM hemorrhoidectomy (Group II). Primary outcome parameter was postoperative pain assessed by Visual Anlougue Scale (VAS) at 24 hours, 7 days and 30 postoperative days.Results: Both the groups were comparable in terms of the demographic characteristics. The mean operation time was significantly lower in group I than group II (19.13±3.42 vs. 28.67±4.54 minutes, p